Intergenerational transmission of risk attitudes: The role of gender, parents and grandparents in Burkina Faso - Mohammad H. Sepahvand; Roujman Shahbazian (Uppsala University, Department of Economics, 2017)
This study investigates the intergenerational transmission of risk attitudes for three risk domains in Burkina Faso. First, our results shows a strong transmission of attitudes from parents to children. Although, estimates from intergenerational transmission of risk attitudes in developing countries should not be compared directly with those from developed countries, our results goes in the same direction as previous literature from Germany. That is risk attitudes are transmitted from; parents to children, local enviorment to children and positive assortative mating of parents strengthens the parents' transmission of attitudes to her child. Second we analyze three generations of risk attitude transmission. Our results indicates that it exist a transmission of risk attitudes from grandparents to their grandchildren. The strength and significance of this socialization decreases when we control for parents risk attitudes. Third, since there are strong gender roles in Burkina Faso, we test if mothers and fathers transmission of risk attitudes on their daughter is the same as on their son. We find that mother's transmission of risk attitudes is stronger on their daughters than sons. For fathers the pattern is reverse. However, our findings show that it exist a heterogenity in the transmission of risk attitudes in male and female dominated risk domains. This gives support for the gender-specific role model hypothesis in terms of risk attitudes.
urn:nbn:se:uu:diva-334076
Keywords: D81; J6; Z1; 330; risk attitudes; inter and multigenerational transmission; socialization; Burkina Faso